Making the Radical University: Identity and Politics on the American College Campus, 1966–1991 - Kalbfleisch, Elizabeth M. (University of Massachusetts Press, 2024)
In the 1960s, professors, students, and activists on the political Left viewed college curricula as useful sites for political transformation. They coordinated efforts to alter general education requirements at the college level to foster change in American thought, with greater openness toward people who had previously been excluded, including women, people of color, the poor and working classes, people with disabilities, and members of the LGBTQ community. Their work reshaped American culture and politics, while prompting a significant backlash from conservatives attempting to, in their view, protect classical education from modern encroachment. Elizabeth M. Kalbfleisch details how American universities became a battleground for identity politics from the 1960s through the 1980s. Focusing on two case studies at Stanford University and the University of Texas at Austin, Making the Radical University examines how curricular changes led to polarizing discussions nationwide around academic standards and identity politics, including the so-called canon wars. Today, these debates have only become more politically charged, complex, and barbed.
Keywords: dept.eng